Soft Security Strategies to Enhance Nepal’s National Security - Acharya, GP (Unity Journal, 2022)
Due to the existing geo-location, geo-political advancement, and geo-strategic cum geo-political interests of powerful nations, the national security milieu of Nepal is constantly under a ‘state of flux’. The changing dynamics of the regional politics have also induced specific geo-political challenges to Nepal’s national security. Nepal has adopted an essence of “Amity with all and enmity with none” on its foreign policy, which is based on the spirit of its long standing ‘Non-Aligned Foreign Policy’. Since Nepal does not acquire any substantial intelligence, counter intelligence or strategic intelligence mechanisms, and has not been fortified with any defense technology yet; Nepal must foster ‘Soft Security Strategies’ that not only enhances its national security, but also help promote its national power capability. Based on various literature reviews, it suggest that the idea of reckoning the impact of soft security approach is an indicative defensive measure of addressing the contemporary security issues in national security. Nevertheless, the main objectives of this research article are to identify the emerging security threat, and assess the ‘Soft Security Strategies’ to enhance Nepal’s national security. This article discourses the geo-strategic prospects in conceiving national security, and explores the potential instruments of Nepal’s national power. The first part deals with apparent challenges to Nepal’s national security, and the second part deals with whether the existing ‘National Security Policy’ is aligned with its corresponding ‘National Security Strategy’. Finally, this paper aims to identify how the small power like Nepal can strengthen the instruments of national power and enhance national security.